Winter City Urbanism : Enabling All Year Connectivity for Soft Mobility - Chapman, David; Nilsson, Kristina L.; Rizzo, Agatino; Larsson, Agneta (International Journal of Environmental Research and Public Health, 2019)
This study explores connectivity for soft mobility in the winter season. Working with residents from the sub-arctic city of Luleå, Sweden, the research examines how the interaction between the built environment and winter season affects people’s use of the outdoor environment. The research questions for this study are, 1) how do residents perceive the effects of winter on an areas spatial structure and pattern of streets and pathways? and 2) what enablers and barriers impact resident soft mobility choices and use of the public realm in winter? Methods used were mental mapping and photo elicitation exercises. These were used to gain a better understanding of people’s perception of soft mobility in winter. The results were analysed to identify how soft mobility is influenced by the winter season. The discussion highlights that at the neighbourhood scale, residents perceive that the winter alters an areas spatial structure and pattern of streets and pathways. It was also seen to reduce ease of understanding of the public realm and townscape. In conclusion, it is argued that new and re-tooled town planning strategies, such as extending blue/ green infrastructure planning to include white space could help better enable all year outdoor activity in winter cities. Validerad;2019;Nivå 2;2019-06-27 (johcin); Artikeln har tidigare förekommit som manuskript i avhandling. ISBN för print edition: 978-3-03921-930-8, 978-3-03921-931-5